Regional changes in vertebra morphology during ontogeny reflect the life history of Atlantic cod (Gadus morhua L.). Issue 6 (15th April 2013) - Fjelldal, Per G.; Totland, Geir K.; Hansen, Tom; Kryvi, Harald; Wang, Xiyuan; Søndergaard, Jens L.; Grotmol, Sindre
Abstract This study examined vertebra formation, morphology, regional characters, and bending properties of the vertebral column of Atlantic cod throughout its life cycle (0–6 years). The first structure to form was the foremost neural arch, 21 days post hatching (dph), and the first vertebra centrum to form – as a chordacentrum – was the 3rd centrum at 28 dph. Thereafter, the notochord centra developed in a regular sequence towards the head and caudal fin. All vertebrae were formed within 50 dph. The vertebral column consisted of 52 (± 2) vertebrae (V) and could be divided into four distinct regions: (i) the cervical region (neck) (V1 and V2), characterized by short vertebra centra, prominent neural spines and absence of articulations with ribs; (ii) the abdominal region (trunk) (V3–V19), characterized by vertebrae with wing‐shaped transverse processes (parapophyses) that all articulate with a rib; (iii) the caudal region (tail) (V20–V40), where the vertebra centra have haemal arches with prominent haemal spines; (iv) the ural region (V41 to the last vertebra), characterized by broad neural and haemal spines, providing sites of origin for muscles inserting on the fin rays – lepidotrichs – of the tail fin. The number of vertebrae in the cervical, abdominal and caudal regions was found to be constant, whereas in the ural region, numbers varied from 12 to 15. Geometric modelling based on combination of vertebra lengths, diameters and intervertebral distances showed an even flexibility throughout the column, except in the ural region, where flexibility increased. Throughout ontogeny, the vertebra centra of the different regions followed distinct patterns of growth; the relative length of the vertebrae increased in the cervical and abdominal regions, and decreased in the caudal and ural regions with increasing age. This may reflect changes in swimming mode with age, and/or that the production of large volumes of gametes during sexual maturation requires a significant increase in abdominal cavity volume.